2005
DOI: 10.1002/cncr.20986
|View full text |Cite
|
Sign up to set email alerts
|

Expression of epidermal growth factor receptor, ERBB2 and KIT in adult soft tissue sarcomas

Abstract: BACKGROUNDLittle is known about the expression of receptor tyrosine kinases in adult soft tissue sarcomas (STS). In the current study, the authors analyzed the expression of epidermal growth factor receptor (EGFR), ERBB2, and KIT in 281 patients with STS who were treated in a single institution. Verification of the presence of an association with prognosis was performed.METHODSThe current study included 281 adult patients with STS of the extremity and trunk who were diagnosed and treated in the National Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
57
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 39 publications
13
57
1
2
Order By: Relevance
“…5,23,24 Previous studies have indicated another potential factor in the Akt/mTOR pathway: the activation of receptor tyrosine kinases or cytokine receptors. Epidermal growth factor receptor (EGFR), 14,25,26 insulin-like growth factor-1 receptor (IGF1R), 14,27 and plateletderived growth factor receptor a (PDGFRa) 6,28,29 have been proven responsible for Akt/mTOR pathway activation in SS, and some preclinical studies have lent credence to targeting this pathway. 6,29 Clinical trials of molecular targeting drugs also have been undertaken in STS.…”
Section: Discussionmentioning
confidence: 99%
“…5,23,24 Previous studies have indicated another potential factor in the Akt/mTOR pathway: the activation of receptor tyrosine kinases or cytokine receptors. Epidermal growth factor receptor (EGFR), 14,25,26 insulin-like growth factor-1 receptor (IGF1R), 14,27 and plateletderived growth factor receptor a (PDGFRa) 6,28,29 have been proven responsible for Akt/mTOR pathway activation in SS, and some preclinical studies have lent credence to targeting this pathway. 6,29 Clinical trials of molecular targeting drugs also have been undertaken in STS.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] In two recent studies of bone and soft tissue neoplasms, EGFR expression was noted in approximately 20% of malignant tumors, with no expression documented in benign lesions, suggesting that EGFR is preferentially expressed in sarcomas. 14,15 However, in general, kinase domain mutations in sarcomas are rare.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Interestingly, recent evidence suggests that EGFR expression is not unique to carcinomas but may be present in malignant bone and soft tissue tumors, with a small subset showing aberrant EGFR gene copy number and/or mutations in the tyrosine kinase domain. [13][14][15][16][17][18] However, the expression, amplification and mutation status of epithelioid sarcoma remains to be characterized.…”
mentioning
confidence: 99%
“…4 There are a growing number of reports describing protein over-expression, gene amplification, and mutation of EGFR in bone and soft tissue tumors. Immunohistochemical analyses by us and others have shown the expression of EGFR in approximately 60% [5][6][7] and the EGFR phosphorylation (activation) in 27%. 7 Furthermore, point mutations in the tyrosine kinase domain, a critical determinant of Gefitinib sensitivity, were found in 13% of the cases.…”
mentioning
confidence: 89%